Comparison of Early versus Delayed Laparoscopic Cholecystectomy for Treatment of Acute Cholecystitis among Iraqi Patients:Clinical Evaluation and Outcomes - Alhillo, Dr. Abdulrazaq Aladdin; Al_Rubaye, Dr. Mohammed Faraj Ali; Al-Malky, Dr. Mohammed Hassan Faraj (Academic Journal of Clinicians, 2023)
Background: Acute cholecystitis (AC) is a common complication of cholelithiasis. Among hospitalized patients with acute diseases of the abdominal organs, AC ranks the second after acute appendicitis. Currently laparoscopic cholecystectomy (LC), considered the gold procedure for treatment of AC. Timing of cholecystectomy remains a topic of debate by many surgeons and scientists in the gastroenterology surgical field. The optimal time to perform laparoscopic cholecystectomy (LC) has been a subject of ongoing controversy. Objective: To compare the outcomes of early versus delayed laparoscopic cholecystectomy for treatment of acute cholecystitis among group of Iraqi patients Patients & methods: A prospective comparative clinical study conducted at Alimamein Al-Kadhimein Medical City in Baghdad-Iraq, during the period from April 2021 to February 2023. Included 84 Iraqi patients presented to our hospital with acute cholecystitis and were assigned into two groups to perform either early or delayed LC according to the decision of the surgeon and the clinical evaluation of each individual case. Results: We found that duration of operation was significantly shorter in early LC group compared to delayed LC group where the mean duration of operation was 60.88 ± 1.55 minutes and 67.29 ± 1.64 minutes, respectively, (P<0.05). Duration of hospital stay was significantly shorter in early LC group compared to delayed LC group, (P<0.05). Rate of conversion to open cholecystectomy was 2.4% and 4.8% in early and delayed LC groups, respectively. Neither significant complications nor mortalities reported among the studied group Conclusion: Early and delayed laparoscopic cholecystectomies were safe procedures without serious complications. Both early and delayed laparoscopic cholecystectomies were almost similar in different variables. Early laparoscopic cholecystectomies had shorten the duration of operation and hospital stay. Further studies are recommended for more precise assessment.